Winning well. Maximizing coach and athlete wellness - Cocchiarella, C.; Adana, C. (Rowman & Litllefield, 2022)
Wellness is complex and powerful. And when wellness is maximized in the sports setting, athletes and coaches alike are set up to succeed.